2022
DOI: 10.3389/fonc.2022.889284
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide 131I-labeled albumin-indocyanine green nanoparticles for synergistic combined radio-photothermal therapy of anaplastic thyroid cancer

Abstract: ObjectivesAnaplastic thyroid cancer (ATC) cells cannot retain the radionuclide iodine 131 (131I) for treatment due to the inability to uptake iodine. This study investigated the feasibility of combining radionuclides with photothermal agents in the diagnosis and treatment of ATC.Methods131I was labeled on human serum albumin (HSA) by the standard chloramine T method. 131I-HSA and indocyanine green (ICG) were non-covalently bound by a simple stirring to obtain 131I-HSA-ICG nanoparticles. Characterizations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
(68 reference statements)
0
5
0
Order By: Relevance
“…In vivo fluorescence imaging and single-photon emission computed tomography (SPECT) imaging in mice confirmed that I-HSA-ICG/ 131 I-HSA-ICG nanoparticles can remain in tumor tissues for 4-6 days, resulting in the most significant ablation effect on tumor cells under 808 nm laser irradiation. 171 In conclusion, nanomaterials offer a promising approach for combining PTT and radiotherapy. The use of PDA nanoparticles and HSA-ICG/ 131 I-HSA-ICG nanoparticles has shown significant inhibition and killing effects on anaplastic thyroid carcinoma (ATC) cells, with further inhibition of cell proliferation when combined with laser irradiation.…”
Section: Multiple Therapy Methods Based On Nanomaterialsmentioning
confidence: 98%
See 1 more Smart Citation
“…In vivo fluorescence imaging and single-photon emission computed tomography (SPECT) imaging in mice confirmed that I-HSA-ICG/ 131 I-HSA-ICG nanoparticles can remain in tumor tissues for 4-6 days, resulting in the most significant ablation effect on tumor cells under 808 nm laser irradiation. 171 In conclusion, nanomaterials offer a promising approach for combining PTT and radiotherapy. The use of PDA nanoparticles and HSA-ICG/ 131 I-HSA-ICG nanoparticles has shown significant inhibition and killing effects on anaplastic thyroid carcinoma (ATC) cells, with further inhibition of cell proliferation when combined with laser irradiation.…”
Section: Multiple Therapy Methods Based On Nanomaterialsmentioning
confidence: 98%
“…In vivo fluorescence imaging and single-photon emission computed tomography (SPECT) imaging in mice confirmed that I-HSA-ICG/ 131 I-HSA-ICG nanoparticles can remain in tumor tissues for 4–6 days, resulting in the most significant ablation effect on tumor cells under 808 nm laser irradiation. 171…”
Section: Nanomaterials In Thyroid Cancer Treatmentmentioning
confidence: 99%
“…Because of the adjustable composition and structure of nanoparticles, a nanoparticle system can be composed of different therapeutic strategies and imaging methods to achieve the synergistic anti-cancer treatment. 109 Zhang et al 40 constructed 131 I-HSA-ICG nanoparticles with 131 I labeled on human serum albumin (HSA) and indocyanine green (ICG) covalently bound to 131 I-HSA. The photothermal conversion efficiency of 131 I-HSA-ICG nanoparticles yields 24.25%, and they have the highest ablation effect on tumor cells under the irradiation of an 808-nm laser (2.5 W/cm 2 ) compared with that of other groups.…”
Section: Nanoparticles Used In the Combination Treatment Of 131 I Rad...mentioning
confidence: 99%
“… 37 BSA and hyaluronic acid (HA) loading remarkably enhances the targeting of drugs and their therapeutic efficacy. Sorafenib, 38 anti-VEGFR2 antibody, 39 indocyanine green, 40 and copper sulfide 41 loaded in mesoporous silica nanoparticles (MSNPs) coated with BSA present excellent outcomes in the treatment of targeted therapy, phototherapy and EBRT.…”
Section: Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation